การพยากรณ์อัตรามรณะของประชากรไทยโดยใช้ตัวแบบลี-คาร์เตอร์ ร่วมกับปัจจัยทางเศรษฐกิจและสาเหตุการตาย - ภัทร สุริยภัทรพันธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This research aims to forecast the mortality rate of the Thai population in the next 20 years (2011-2030) by using the estimated model generally known as Lee-Carter model, with gross domestic product (GPD), unemployment rate, and the specific cause of death, including neoplasm, certain infectious and pasasitic diseases, external cause of morbidity and mortality other accidents, diseases of the circulatory system, and diseases of the respiratory system. Preliminary results show that all of variables (k_t, GDP, unemployment rate and specific cause of death ) are stationary data at first difference at significance level 0.01. For males, cointegration is found between mortality index and mortality rate from neoplasms, certain infectious and parasitic diseases , and diseases of the respiratory system. For female, cointegration is found between mortality index and mortality rate from neoplasms, and certain infectious and parasitic diseases. In the case of the forecasting, found that the forecasting mortality rates have increased by the exponential age. For both male and female, the forecasting mortality will be slightly reduced by increasing the number of years.